Analisa Kebijakan Pemerintah Kota Medan Tahun 2017-2020 Terkait Ancaman Pengangguran Pasca Kenaikan Inflasi - Adi Wilyanto; Angelina Julia Renaldi; Eni Valentina; Richmond, Richmond; Rieza Melinda (Journal of Management and Social Sciences, 2022)
The relationship between the inflation rate and the unemployment rate affects a country's mix of fiscal and monetary policy decisions to achieve better economic conditions. The purpose of this study is to analyze the Medan City Government's policy regarding the threat of unemployment after the increase in inflation using data from 2017-2020. The data collection method used is library research method. In the results of the study, the number of unemployed from 2017 decreased by 9.46%, in 2019 it increased by 8.53 and in 2020 the increase reached 10.74%. In 2020, Indonesia was affected by the covid-19 pandemic which caused the country's economy to decline. This is one of the factors for the increasing number of unemployed and the inflation rate from 2017 has decreased until 2020. Inflation must be prevented immediately by means of policies from the government, namely by receiving and state budget expenditures to maintain currency stability with the aim of improving the welfare of the people in a country.